Simulating impacts of nitrogen fertilization using DAYCENT to optimize economic returns and environmental services from bioenergy sorghum production. (21st September 2020) - Wang, Yong; Dou, Fugen; Paustian, Keith H.; Del Grosso, Stephen J.; Storlien, Joseph O.; Wight, Jason P.; Hons, Frank M.
Abstract: Inappropriate nitrogen (N) fertilization rate could cause yield and economic losses and negative environmental impacts. This study was conducted to explore optimum N rate for a promising biofuel crop ‐ bioenergy sorghum [ Sorghum bicolor (L.) Moench]. The biogeochemical model, DAYCENT, was verified with an eight‐year field trial and then used to simulate the long‐term (35 years) effects of N fertilization on aboveground biomass carbon (C), soil organic C (SOC), carbon dioxide (CO2 ), and nitrous oxide (N2 O) emissions. Associated with the simulated metrics, N use efficiency (NUE), net greenhouse gas (GHG) emissions, and net economic return to N (RTN) were calculated to determine the optimum N rate. The model was capable of reproducing the field measurements with r 2 of 0.57, 0.47, 0.55, and 0.34 for aboveground biomass C, SOC, CO2, and N2 O, respectively. Projection with 0–350 kg N ha −1 fertilization in increments of 70 kg N ha −1 indicated positive responses of aboveground biomass C and SOC to increasing N but with little increase above 140 kg N ha −1 . Declining NUE and increasing net GHG emission at field scale were predicted as N rate increased. When considering GHG mitigation from fossil fuel replacement, net GHG emission decreased first and leveled off at a N rate of 70–140 kg N ha −1 before increasing. Net economic RTN increased first and peaked when N rate was around 140 kg N ha −1 before decreasing. Fertilization at 140 kg N ha −1 was found to be optimal when using both GHG mitigation and economic criteria.